Enhancing the quality of animal meat products by combining plant-based marinations and thermal processes: a treatise - OKPALA, Charles Odilichukwu R.; HASSANI, Mouandhe IMAMOU; KORZENIOWSKA, Małgorzata; GUINÉ, Raquel Pinho Ferreira (Food Science and Technology, 2023)
Nowadays, natural preservatives, specifically involving marinades, are being applied to meat products to enhance various quality attributes. The need for food preservation has continually strengthened the processing of meat products. Besides the global production of bovine, porcine, ovine, and caprine animals, including poultry, that varies across continents, meeting the demands/needs of ever-increasing (global) population remains the focus. The growing consumer health awareness alongside intensifying global competition by meat producers cumulatively strengthens the call for healthier products, including preservation strategies. However, as published experimental/synthesized literature involving animal meat products, plant-based marination, and thermal processes continues to grow, there is a need to supplement existing information. Therefore, this treatise aims to discuss how the quality of animal meat products has been enhanced through plant-based marinations and thermal processes, drawing from plant-based marination: some key examples and usefulness; marination/marinades: briefs on preparation and applications; major thermal processes applied to marinated meat products; as well as quality implications of thermally processed marinated meat products. In certain instances, either marination would aid heat processing or vice versa, while in others, thermal processing may well be detrimental to marination.